2005
DOI: 10.3171/foc.2005.18.4.5
|View full text |Cite
|
Sign up to set email alerts
|

History of infection control and its contributions to the development and success of brain tumor operations

Abstract: Before advancements in infection control, only conditions that brought patients near death warranted the risk of surgical intervention. If patients survived the operation, infection was nearly inevitable and death by overwhelming sepsis was knocking at their door. In the late 19th century, with the development of germ theory by Louis Pasteur and its subsequent application to surgical sterility by Joseph Lister, surgeons were able to operate with a substantially reduced risk of infection. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 12 publications
0
28
0
4
Order By: Relevance
“…The advent of germ theory by Louis Pasteur and its subsequent application to surgical sterilization by Joseph Lister in the late 19th century allowed for a marked reduction in the rates of postoperative sepsis, resulting in an expansion of the depth and breadth of operative neurosurgical procedures that could be performed safely [10][11][12][13]. The safety of neurosurgical procedures was further enhanced by the clinical application of Alexander Fleming's original penicillin mold extract in the 1940s in the operating room through the work of Howard Florey and Ernst Chain, allowing for nonemergent lesions to be treated neurosurgically with a previously unattainable level of postoperative safety, thereby opening the door for elective neurosurgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of germ theory by Louis Pasteur and its subsequent application to surgical sterilization by Joseph Lister in the late 19th century allowed for a marked reduction in the rates of postoperative sepsis, resulting in an expansion of the depth and breadth of operative neurosurgical procedures that could be performed safely [10][11][12][13]. The safety of neurosurgical procedures was further enhanced by the clinical application of Alexander Fleming's original penicillin mold extract in the 1940s in the operating room through the work of Howard Florey and Ernst Chain, allowing for nonemergent lesions to be treated neurosurgically with a previously unattainable level of postoperative safety, thereby opening the door for elective neurosurgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…The use of gowns, masks, and gloves was introduced in the 1880s to prevent infections and work by Florence Nightingale during the Crimean War emphasized sanitation and hygienic practices, methods still in effect today (5,19).…”
Section: Modern Microbiology Antiseptics Infection Control and Antmentioning
confidence: 99%
“…[1] This book outlines the practice of using alcoholic beverages and turpentine for wound management. [10] In 1944, Cairns insufflated penicillin and sulfamethazene powder onto war wounds and reported that his neurosurgical experience with topical antibiotic prophylaxis was generally helpful. [2] Perhaps Pennybacker et al .…”
Section: Discussionmentioning
confidence: 99%